2008
DOI: 10.1159/000151368
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in Disease-Free Survivors of Cervical Cancer Compared with the General Female Population

Abstract: Objectives: We aimed to investigate the prevalence of comorbidities in cervical cancer survivors compared with the general population and to identify risk factors and impact on their quality of life (QoL). Methods: 860 female cervical cancer survivors enrolled at six tertiary hospitals and 994 women from the general population were surveyed on current comorbidities and QoL (EORTC QLQ-C30 and QLQ-CX24). Results: Compared with the general female population, the cervical cancer survivors reported higher prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 80 publications
(41 reference statements)
1
25
2
Order By: Relevance
“…In the present study, the results may have been affected by the fact that more than 50% of participants were aged ≥50 years, and more than 50% had less than a middle-school level of education, so the socioeconomic differences might not be significant. The SEER stage (used to categorize localized primary cancer and metastasized cancer), and the Charlson Comorbidity Index (used to assess the effects of comorbid conditions) revealed no significant differences in depression and suicidal ideation; this differs from the results of previous studies (Recklitis et al, 2010;Shin et al, 2008). The difference might have been related to the fact that we could not stratify the patients by type of cancer because the number of patients with each type of cancer was so small, and previous studies might have focused on specific types of cancer.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In the present study, the results may have been affected by the fact that more than 50% of participants were aged ≥50 years, and more than 50% had less than a middle-school level of education, so the socioeconomic differences might not be significant. The SEER stage (used to categorize localized primary cancer and metastasized cancer), and the Charlson Comorbidity Index (used to assess the effects of comorbid conditions) revealed no significant differences in depression and suicidal ideation; this differs from the results of previous studies (Recklitis et al, 2010;Shin et al, 2008). The difference might have been related to the fact that we could not stratify the patients by type of cancer because the number of patients with each type of cancer was so small, and previous studies might have focused on specific types of cancer.…”
Section: Discussioncontrasting
confidence: 84%
“…By comprehensively incorporating the significant factors identified in previous studies (Charlson et al, 1987;Miller, 2000;Pirkis, 2000;Akechi et al, 2002;Akechi et al, 2002;Amir., 2002;Bruce et al, 2004;Pirkola, 2004;Bjorkenstam et al, 2005;Misono et al, 2008;Shin et al, 2008;Park et al, 2009;Ahn et al, 2010;Fanger et al, 2010;Recklitis et al, 2010;Shim, 2010;Shin et al, 2010;Mitchell et al, 2011), this study analyzed the influential parameters using depression and suicidal ideation as dependent variables, and sociodemographic characteristics, health-related behavior, clinical conditions, and quality of life as independent variables. Age, education, income (monthly income after cancer diagnosis), and marital status were categorized as sociodemographic characteristics, and smoking and alcohol consumption represented health-related behavior.…”
Section: Variablesmentioning
confidence: 99%
“…Previous studies found no significant difference in the prevalence of hypertension between cancer survivors and non-cancer survivors (Enright et al, 2010),slightly higher prevalence in cancer survivors according to cancer types (Shin et al, 2008;Weaver et al, 2013), or specific treatment methods (Jain et al, 2007;Valentova et al, 2011). Hypertension was the most frequent comorbid condition treated in cancer survivors (Goytia et al, 2009), and there is a widespread need for the management of chronic diseases and related risk factors to reduce the late adverse effects of chemotherapy and radiation (Daher et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…With the increasing number of cancer survivors, evaluation and management of their chronic comorbid conditions have become important issues (Ogle et al, 2000). Hypertension is the most common comorbidity in cancer survivors, with a prevalence of 20%-65% (Ogle et al, 2000;Park et al, 2006;Shin et al, 2008;Braithwaite et al, 2009). Prevalence of hypertension at the time of cancer diagnosis is similar to that in the general population, however, the much higher rate is observed after treatment such as chemotherapy (Mouhayar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation